X-Ray Diffraction Line Broadening of Irradiated Zr-2.5Nb Alloys - Malcolm Griffiths (Metals)
The evolution of the mechanical properties of Zr-2.5Nb pressure tubing during irradiation is dependent on dislocation loop densities that are represented by the broadening of X-ray diffraction lines. Empirical models for the integral breadth of the diffraction peaks as a function of operating conditions have been developed to predict the mechanical properties of CANDU reactor pressure tubes as a function of fast neutron flux, time and temperature. Apart from predicting mechanical property changes based on integral breadth measurements, a new model has been developed to retrospectively deduce abnormal operating temperatures of ex-service pressure from the measured line broadening. The application of integral breadth measurements to assess mechanical properties and temperature variations in pressure tubes is described and discussed in terms of the implications for pressure tube integrity.